ISLAM AND LOCAL CULTURE (Living Qur'anic Studies In The Ngeruwat Bumi Culture In Balung Village) - Miftahus Sa’diyah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
This paper tries to explain the phenomenon that has become a tradition of Muslim society. A tradition that presents the Qur'an in the midst of people's life or it is referred to as "living quran". Ngeruwat Bumi is one of the traditions of the many phenomena of Muslims in the suro month or Muharram in presenting the Qur'an in everyday life. The thing that makes this tradition unique is the tumpeng, which before the arak surrounds the surrounding environment is read prayer beforehand which is led by elders and religious leaders. Tumpeng in the Ngeruwat Bumi tradition itself consists of 7 kinds, namely: white rice cone, yellow rice, mending polo, fruit, leaf vegetables and cone vegetables such as eggplant, carrots etc. Based on the reality above, the focus of this research is 1) What is the practice and contribution of the community to the Ngeruwat Bumi tradition in Balung Village? 2) What is the meaning of the Ngeruwat Bumi tradition in the Balung community perspective? In this study researchers used a phenomenological approach, and interview observation methods. So that the results of this study indicate that: 1) How is the practice of the Ngeruwat Bumi tradition carried out by the Balung community as well as the huge community contribution to the celebration of Earth Grownup in every month of Suro. Given that lately people think that God is showing his power by shaking the earth. Realizing this, many people contribute to the tradition. 2). Society believes in the values contained in the tradition. Like rejecting reinforcements, starting a new page with kindness, introducing the tradition to the younger generation, and others.